2016
DOI: 10.1088/0264-9381/33/9/095007
|View full text |Cite|
|
Sign up to set email alerts
|

Gravitational deflection of light and massive particles by a moving Kerr–Newman black hole

Abstract: The gravitational deflection of test particles including light, due to a radially moving Kerr–Newman (KN) black hole with an arbitrary constant velocity that is perpendicular to its angular momentum, is investigated. In harmonic coordinates, we derive the second post-Minkowskian (2PM) equations of motion for test particles, and solve them by high-accuracy numerical calculations. We then concentrate on discussing the kinematical corrections caused by the motion of the gravitational source to second-order deflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 52 publications
7
53
0
Order By: Relevance
“…Appendix B: Derivation of Eqs. (39) and (40) We begin by expanding f c to the first order of (1 − v). It is seen that f c (h, v) and ω c (h, v) can be solved from Eqs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Appendix B: Derivation of Eqs. (39) and (40) We begin by expanding f c to the first order of (1 − v). It is seen that f c (h, v) and ω c (h, v) can be solved from Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…The coefficients ω 1,v , ω 1,f can be solved from these equations, and their solutions are given in corresponding terms in (39). ω 4 can be handled similarly and the result is also given in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of the deflection angle of massive particles in the spacetime of rotating naked singularities requires integration of the first derivative of the azimuthal shift function dφ/dr, as follows from Eq. (75). Since, we are expecting small deviation in the orbital motion of the particle, we will consider only terms with the most significant contribution, for simplicity.…”
Section: A Deflection Angle By Rotating Naked Singularitiesmentioning
confidence: 99%
“…[5]. Recently, He and Lin [10] considered the gravitational deflection of relativistic massive particles and light caused by a moving Kerr-Newman source numerically, and found that the second-order Schwarzschild contribution was in agreement with the former. This consistency was further confirmed by the analytical calculation via an iterative technique [11].…”
Section: Introductionmentioning
confidence: 99%